Muscle dysfunction in axial spondylarthritis: the MyoSpA study - Neto, A. (2022)
Objective We aimed to investigate muscle physical properties, strength, mass, physical performance, and the prevalence of sarcopenia in patients with axial spondylarthritis (axSpA) compared to the healthy controls (HC). Methods We performed a cross-sectional study on 54 participants: 27 patients with axSpA and 27 HC, matched by age, gender, and level of physical activity. Muscle physical properties (stiffness, tone and elasticity), muscle strength (five-times sit-to-stand [5STS] test), muscle mass, physical performance (measured through gait speed) and sarcopenia were compared between the groups. Linear regression models were conducted allowing adjustment for relevant variables. Results Patients with axSpA (mean age 36.5 (SD 7.5) years, 67% males, mean disease duration 6.5 (3.2) years) had no significant difference in segmental muscle stiffness, tone or elasticity, compared with the HC, despite showing a slight numerically higher lower lumbar (L3-L4) stiffness [median 246.5 (IQR 230.5–286.5) vs. 232.5 (211.0–293.5), p=0.38]. No participants presented sarcopenia. Patients with axSpA, compared to the HC, had lower total strength [B=1.88 (95% CI 0.43;3.33)], as well as lower strength in the upper (B= -17.02 (-27.33;-6.70)] and lower limbs [B= -11.14 (-18.25;-4.04)], independently of muscle physical properties. Patients had also significantly lower gait speed than the HC [B= -0.11 (-0.21;-0.01)], adjusted for muscle mass, strength and muscle physical properties. Conclusion Young axSpA patients with a relatively short disease duration presented similar segmental muscle physical properties as the HC and had no sarcopenia. Patients with axSpA had reduced physical performance and lower strength compared to the HC, despite normal muscle mass, suggesting a possible muscle dysfunction. Gait characteristics may be a potential biomarker of interest in axSpA.